2015
DOI: 10.4067/s0717-97072015000100005
|View full text |Cite
|
Sign up to set email alerts
|

A Low-Cost and High-Yield Production of Magnetite Nanorods With High Saturation Magnetization

Abstract: Nanopowders of single-crystalline rod-like magnetite have been synthesized in a glycerol-water system under hydrothermal condition by using the goethite (α-FeOOH) precursor. The influence of different reaction parameters on the morphology and composition of the products have been investigated. The structure, morphology and magnetic properties of the products were characterized by X-ray diffraction (XRD), field emission scanning electron microscope (FESEM), transmission electron microscope (TEM) and superconduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 15 publications
2
9
0
Order By: Relevance
“…observed lattice spacing of 0.298 nm, which match well with the (220) lattice planes and confirmed that the nanorods grew along (110) direction [50,42]. Fig.…”
Section: Wang Et Al Observed a Lattice Spacing Of 048 Nm For Fe3o4 supporting
confidence: 68%
See 1 more Smart Citation
“…observed lattice spacing of 0.298 nm, which match well with the (220) lattice planes and confirmed that the nanorods grew along (110) direction [50,42]. Fig.…”
Section: Wang Et Al Observed a Lattice Spacing Of 048 Nm For Fe3o4 supporting
confidence: 68%
“…Crystallography of Fe3O4 naanoparticles are inverse-spinel crystal with face-centered cubic, structures (Fd3m space group) [41]. Several work have reported the elongation of magnetite iron oxide crystal based on (110) plan [42][43][44], (100) plan [45,46], and (111) plan [47,48], which formed nanorods morphology.…”
Section: Proposed Formation Mechanism Of Nanoparticles With Differentmentioning
confidence: 99%
“…3 ). The magnetization value of nanorod is much larger than the previous reported pure hematite alone [ 40 , 41 ], which could due to the ferromagnetic nature of magnetite, of which the magnetization in pure form can reach up to 100 emu/g [ 42 ].
Fig.
…”
Section: Resultsmentioning
confidence: 84%
“…[48][49][50]. The aqueous co-precipitation of Fe 2+ and Fe 3+ by a base, usually sodium hydroxide or aqueous ammonia, is the well-known method which is usually carried out for synthesizing the magnetite nanoparticle [51]. This method is the most scalable chemical synthesis routes which results in iron oxide nanospherical crystal.…”
Section: Magnetic Nanorodsmentioning
confidence: 99%